Entrepreneurship as a Guide to Islamic Da'wah in the Business Concept of Rasulullah ﷺ : Wirausaha Sebagai Wasilah Dakwah Islam Dalam Konsep Usaha Rasulullah ﷺ - Husnul Khatimah; Annisa Nur Fadhillah; Anis Rahayu; Annisa Habsah Maualana (QULUBANA: Jurnal Manajemen Dakwah, 2024)
Nowadays, da'wah can be done while running a business or entrepreneurship. This research aims to find out how entrepreneurship as an intermediary for Islamic preaching in the concept of the Prophet's business which aims to emphasize that entrepreneurship is not only for worldly gain but must be able to take a role in preaching to spread Islam. The literature method and descriptive qualitative approach are the methods used in this research. This study outlines the findings of how to find out the values of da'wah that Rasulullah Shallallahu 'Alaihiwa Sallam exemplified as a reliable business expert, the best business teacher of all time and even a great statesman and world leader can be done by entrepreneurship, both in terms of trading, and creating jobs. Entrepreneurial activities can be used as one of the wasilah da'wah noble purpose in line with the provisions of shariuat as an effort to improve the welfare of the ummah, increase economic progress, give birth to a culture of high work ethic includes noble character qudwah us, namely amanah, shiddiq, tabligh and fathanah. In entrepreneurship, ethics and procedures are needed to run a business based on sharia principles, so that it gets a blessing from Allah and benefits many people.